2006
DOI: 10.1109/titb.2005.855552
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monitoring Technology in Assisted Living: Outcome Pilot

Abstract: This paper describes a study designed to assess the acceptance and some psychosocial impacts of monitoring technology in assisted living. Monitoring systems were installed in 22 assisted living units to track the activities of daily living (ADLs) and key alert conditions of residents (15 of whom were nonmemory care residents). Activity reports and alert notifications were sent to professional caregivers who provided care to residents participating in the study. Diagnostic use of the monitoring data was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 10 publications
0
84
0
Order By: Relevance
“…The first paper included in the review dated back to 1997, indicating that Celler"s study of 1995 could be considered as one of the earliest of this type. Of the 74 full articles reviewed, only the 4 [7,8,9,10] shown in Table 2 were concerned with trials involving over 20 subjects whilst a further 21 papers reported trials with fewer than 20 subjects. The full distribution of reported trials is then as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first paper included in the review dated back to 1997, indicating that Celler"s study of 1995 could be considered as one of the earliest of this type. Of the 74 full articles reviewed, only the 4 [7,8,9,10] shown in Table 2 were concerned with trials involving over 20 subjects whilst a further 21 papers reported trials with fewer than 20 subjects. The full distribution of reported trials is then as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fall watch remains active until the participant leaves the bedroom and bathroom area (indicated by reported motion activity outside the bathroom or bedroom) or returns to bed (indicated by movement followed by detection of the pulse). With no motion detected after exiting the bed, the Data Manager can connect to the facility's pager system and sent the participant's identification code appended with the code for a "possible fall" to the caregiver [17]. Fig.2.…”
Section: Technology and Tiger Placementioning
confidence: 99%
“…The knowledge-acquired rules were also compared to automated supervised learning methods including, decision trees and Random Forests, and were found to be more reliable [16]. The acceptance, utility, and impact of the system on the different stake-holders including older adults, professional caregivers and informal caregivers were evaluated in a series of pre-experimental pilot studies in different care settings and presented in [17][18][19][20].…”
Section: ) Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] As a caretaker will be there then those will follow doctor instructions and then treat people. Many of researchers are investigated and then a design an architecture for s mart health protection with the comb ination of computer, netwo rking and bio medical fields.…”
Section: Introductionmentioning
confidence: 99%